Product development of Wedang Seroja (Lemongrass, Rosella and Ginger) Tea Bag - Syahputri, Gusti Ananda; Devinta, Farinsia Dara; Fertiasari, Rini; Maghfira, Lativa Lisya (Central Research Institute For Agriculture, 2024)
Wedang is a beverage that comes from a blend of spices that are often found in Indonesia. The mixture of spices used in making wedang can affect the taste, color and content inside. One of the wedang that can be found is wedang seroja, a wedang that made from a mixture of lemongrass, rosella and ginger in varying proportions. Wedang seroja tea bag is an innovation to serve the wedang easily. The proportion of spices in the mixture can influence the characteristics of the mixture of spice and steeping water. Therefore, this research aims to develop a wedang seroja tea bag product and observe the characteristics of the product by physical and chemical analysis of the dry spice mixture and steeping water of wedang seroja tea bag. The sample was made in three repetition and each sample were analyzed three times (triplo). The results of the study carried out on wedang tea bag with a composition of 20% lemongrass, 70% rosella and 10% ginger, it was found that the wedang tea bag seroja dry spice mixture had a moisture content of 15.90% and an ash content of 6.37% while the steeping water has a pH of 2.10 and objective color testing results with an L value of 43.56, a value of +23.25, and b value of +21.56. The 70% of rosella in the dry spices mixture of wedang seroja tea bag has a big role on the product characteristics.